Validity and reliability of scales on intrapersonal, interpersonal and environmental factors associated with physical activity in Brazilian secondary students - Valter Cordeiro Barbosa Filho; Cassiano Ricardo Rech; Jorge Mota; José Cazuza de Farias Júnior; Adair da Silva Lopes (Universidade Federal de Santa Catarina, 2016)
This study aimed to examine the validity and reliability of scales of intrapersonal, interpersonal, and environmental factors associated with physical activity (PA) in secondary students. Two cross-sectional studies were conducted with students in 7th to 9th grades form secondary schools in order to test the validity, internal consistency (n = 1,178, 51.4% were boys), and test-retest reproducibility (n = 194, 56.2% were boys) of the instrument. Factors associated with PA (attitude, self-efficacy, social support of friends, parents and the school's teachers, as well as the perceived neighborhood environment and perceived school environment) were measured. The confirmatory factor analysis and Spearman correlation between the scales and the weekly time spent in moderateto-vigorous PA (measured by questionnaire) were applied to test the construct validity. For reliability, the Cronbach's α (internal consistency), composite reliability (CR) and intraclass correlation coefficient (ICC for test-retest reproducibility) were applied. The confirmatory factorial analysis showed five one-dimensional and two two-dimensional (self-efficacy and perceived environment) scales, with factor loadings ranging from 0.46 to 0.85. Significant and positive correlations between almost all scale scores and moderateto-vigorous PA (p<0.05) were found. The Cronbach's α and CR were greater than 0.70 in almost all scales (except perceived school environment, α and CR of 0.61) and the ICC ranged from 0.62 (parental social support) to 0.70 (self-efficacy). In conclusion, the scales showed acceptable validity and reliability and can be used for measuring of PA correlates in elementary students.